Pharmacological Assessment of the Antiprotozoal Activity, Cytotoxicity and Genotoxicity of Medicinal Plants Used in the Treatment of Malaria in the Greater Mpigi Region in Uganda - Schultz, Fabien; Osuji, Ogechi Favour; Nguyen, Anh; Anywar, Godwin; Scheel, John R.; Caljon, Guy; Pieters, Luc; Garbe, Leif-Alexander (Frontiers in Pharmacology, 2021)
We investigated the potential antimalarial and toxicological effects of 16 medicinal plants frequently used by traditional healers to treat malaria, fever, and related disorders in the Greater Mpigi region in Uganda. In addition, the traditional healers indicated that P. hadiensis is used as a ritual plant to boost fertility and prepare young women and teenagers for motherhood in some Ugandan communities where a high incidence of rapidly growing large breast masses in young female patients was observed (not necessarily breast cancer). We present results from various in vitro experiments performed with 56 different plant extracts, namely, (1) evaluation of traditional use by identifying promising plant extract candidates using a heme biocrystallization inhibition library screen; (2) follow-up investigation of antiprotozoal effects of the most bioactive crude extracts against chloroquine-resistant P. falciparum K1; (3) cytotoxicity counterscreen against human MRC-5SV2 lung fibroblasts; (4) genotoxicity evaluation of the extract library without and with metabolic bioactivation with human S9 liver fraction; and (5) assessment of mutagenicity of the ritual plant P. hadiensis. A total of seven extracts from five plant species were selected for antiplasmodial follow-up investigations based on their hemozoin formation inhibition activity in the heme biocrystallization assay. Among other extracts, an ethyl acetate extract of L. calostachys leaves exhibited antiplasmodial activity against P. falciparum K1 (IC50 value: 5.7 µg/mL), which was further characterized with a selectivity index of 2.6 (CC50 value: 14.7 µg/mL). The experiments for assessment of potential procarcinogenic properties of plant extracts via evaluation of in vitro mutagenicity and genotoxicity indicated that few extracts cause mutations. The species T. asiatica showed the most significant genotoxic effects on both bacterial test strains (without metabolic bioactivation at a concentration of 500 µg/plate). However, none of the mutagenic extracts from the experiments without metabolic bioactivation retained their genotoxic activity after metabolic bioactivation of the plant extract library through pre-incubation with human S9 liver fraction. While this study did not show that P. hadiensis has genotoxic properties, it did provide early-stage support for the therapeutic use of the medicinal plants from the Greater Mpigi region.